(untitled) (Modern education and development, 2025)
Language adapts to social and cultural contexts through styles, registers, and genres, shaping communication. This paper examines their roles in discourse, social interaction, and cultural identity, emphasizing their importance for linguistic competence and cross-cultural communication. Язык адаптируется к социальным и культурным контекстам через стили, регистры и жанры, формируя коммуникацию. В статье рассматривается их роль в дискурсе, социальных взаимодействиях и культурной идентичности, подчеркивая их значение для языковой компетенции и межкультурного общения.